Joint interpretation of gravity and airborne magnetic data along the Calama-Olacapato-Toro fault system (Central Puna, NW Argentina): Structural and geothermal significance. (January 2023) - Ahumada, M.F.; Sánchez, M.A.; Vargas, L.; Filipovich, R.; Martínez, P.; Viramonte, J.G.
Highlights: The study area is located in the region defined as Central Puna Energy Hub. The gravity and magnetic of the area were conducted in an attempt to delineate geological structures controlling the circulation of the fluids and estimate the geothermal field extent. The low density and susceptibility contrast can be related to a combination of high temperatures and steam versus liquid-filled pores and fractures. Gravity and magnetic inversion show low density and susceptibility contrast of rocks associated with volcano-sedimentary rocks filling a volcano-tectonic depression, limited by the Antuco and Pompeya N-S thrust faults, westward and eastward respectively. Geological conceptual model based on the 2-D forward modelling of geophysical data, allows better knowledge and comprehension of hydrothermal fluids circulation in the middle of the Central Puna, in northwest Argentina. Abstract: Here, we present new gravity and airborne magnetic geophysical data from a preliminary exploration along the western sector of the NW-striking Calama-Olacapato-Toro fault system. This area is located in the back-arc region of the Central Andes (NW, Argentina) and is considered as a high potential geothermal area within the Central Puna Energy Hub. The gravity and magnetic modelling was carried out with the aim of delineating geological structures that control the geothermal manifestations and estimate the geothermal field extent. Gravity data were separated into regional and residual components. Then, a 2-D gravity and magnetic modelling was carried out through the 2-D GM-SYS - Oasis Montaj software in order to build an inversion model that adjusts the residual gravimetric and magnetic anomalies observed on the surface. The resultant model was also fitted taking into consideration previous electrical resistivity studies, surface manifestations, geology, and geological structures. Bouguer anomalies are negative in the range of -411 to -304 mGal, while magnetic anomalies have a range of − 127 to 15 nT, in the central part of the study area. Hot springs correlate with low residual Bouguer and magnetic anomalies located on the Calama-Olacapato-Toro lineament, and are related to the alteration zone and the main damage zone. Gravity and magnetic inversion show low density and susceptibility contrast of rocks associated with volcano-sedimentary rocks filling a volcano-tectonic depression, limited by the Antuco and Pompeya N-S thrust faults, westward and eastward respectively. The low density and susceptibility contrast can be related to a combination of high temperatures and steam versus liquid-filled pores and fractures. Hence, this geological conceptual model based on the 2-D forward modelling of geophysical data, allows better knowledge and comprehension of hydrothermal fluids circulation in the middle of the Central Puna, in northwest Argentina.